Pedagogy of Hospitality: Critical Reflection on Teaching Language to Migrants - Andrés González Novoa; María Lourdes C. González Luís; Pedro Perera Méndez; María Daniela Martín Hurtado (Education Sciences)
The Critical Pedagogies Research Team (PEDACRI-ULL) participates in the Program for the Inclusion of Migrants at Risk of Social Exclusion (PIPE) 2023-1-ES01-KA220-ADU-000160578, funded by the European Union. This project aims to design, implement and promote a transnational cooperation network to enhance the skills and competencies of migrants. Its purpose is to provide an educational response aligned with the European Commission’s Pact on Migration and Asylum.. Among its objectives, the program develops tools for professionals and institutions working with migrants, fostering collaborative learning to envision a culture of peace. In this essay, we explore the Pedagogy of Hospitality through critical pedagogies and the dialogue of knowledge. We propose a model of migrant citizenship based on an interlinguistic didactic relationship that promotes intercultural coexistence, grounded in an ethic of miscegenation. Furthermore, we advocate language teaching as a universal right and argue that hospitality should not be seen as an act of generosity but as a moral duty. This perspective supports an inclusive and just education, where language serves as a bridge for integration and mutual recognition.